Parents’ and Students’ Perception on Learning in the Age of Industrial revolution 4.0 at SDN 22 Inpres Pali, Tana Toraja - Ilyas Kala Lembang; Rusli Rusli; Dewi Artati Padmo Putri (Universitas Muhammadiyah Enrekang, 2022)
Learning is currently slowly leading to a major change, namely the industrial revolution 4.0. The purpose of this study was to describe parents' learning perceptions in the Industrial Revolution 4.0 era and students' learning perceptions in the Industrial Revolution 4.0 era at SDN 222 Inpres Pali, Tana Toraja Regency. The approach used in this research is a mixed methods model with a sequential exploratory model. The mixed methods sequential exploration model is a research method that combines qualitative and quantitative approaches to obtain valid data. The data in this study consisted of two data sources, namely primary and secondary data. Qualitative results were obtained in a structured way, the researcher conducted interviews with 4 parents, representatives of guardians of lower and upper grade students. Also, among the students involved, there were 4 people representing upper and lower classes. Several themes were formulated in the results of the study to represent the responses of the informants, including school descriptions, usage, understanding, learning practices, positive and negative impacts, and views on learning with technology and communication tools. Quantitative data from questionnaire data. From the results and discussion of parents' and students' perceptions of learning in the age of Industrial Revolution 4.0, SDN 222 Inpres Pali students and parents to use technology, communication and information tools positively, to learn with technology and means of communication had a positive impact on parents and students. The biggest benefit is to help students overcome learning difficulties, such as teachers and parents.